Entre os “imprescindíveis” e os “redundantes” : olhares sobre constituição de espaços e mundo do trabalho rural na região Norte de Mato Grosso do Sul contemporâneo - Feitosa, Beatriz dos Santos de Oliveira (2016)
This work aims to give visibility to the logic of modernity that underlies the speeches of progress and development, presenting the permanence of some speech production in distinct moments of Brazilian history which gave the shades of territorial occupancy in Brazil and set the feature of social positions occupied by human groups. The dynamics of territorial occupancy on Northern region of Mato Grosso do Sul – space addressed on this research -, allow us to conclude that there was a making of territorialities that determined labor relations. The exclusion of workers derived from the project of modernity and, according to the shape it took in Brazil, it created contingents of “redundant” humans. The theoretical-discursive prop for the actions endeavored by the Federal Government on the region was about development and progress, which caused the migration of a human contingent that, deterritorialized from their original place, launched the search for new territorialities in which the state of Mato Grosso do Sul was one of their possibilities. The years that came after 1970 were defined by great investment by Federal Government in occupancy of Midwest, which allowed such assertion was the documented work, the journals, the oral sources and the data collect of IBGE and SUDECO’s archive, the document corpus explicated the great transformations lived on Midwest, especially in the state of Mato Grosso, split in 1979, wherein were consubstantiated some socio-spatial transformations. The sale of lands resulting from the projects of colonization by Federal Government created the ideal of New Border, in which a plan for development was organized, that is the basic element of the definitions and guidelines of regional economy. Investing on development of the region was a form, regarding to discursive field, to improve the life conditions for the population and rationalize the use of spaces and natural resources. However, what occurred was the extermination of Indian nations, the exclusion of workers by the processes of technicization and agricultural mechanization plus the spatial transformation in extensive fields for agricultural production with monocultural profile. The space of agricultural New Border was redefined through a fallacious speech, because the setting to the territory was a privilege given to agricultural growers who migrated from Southern region of the country, mainly from the state of Paraná, who arrived already capitalized in Mato Grosso do Sul and also counted on resources by the Federal Government. The crisis of the modernity project imposes the necessity of a new pattern of development that takes in consideration the production of “human waste” and the existence for future generations through practices that valorize the food production rather than a model of growth predatory of human issues and of environment.